The Image of Incriminated Masculinity in Crime Narratives - A Hegemonic Approach - Olga Pankalla (Horyzonty Wychowania, 2025)
RESEARCH OBJECTIVE: The aim of this article is to characterize the portrayal of incriminated masculinity in crime narratives.